Difficulties learning reading skills for kindergarten students from the perspectives of kindergarten teachers, administrators, and supervisors - Sawalha, Worood Tayseer; Habayeb, Ali Hassan (Journal of Educational and Psychological Sciences, 2023)
The study aimed to reveal the difficulties of learning reading skills among kindergarten students from the viewpoints of kindergarten teachers, principals, and supervisors. The researcher followed the mixed approach (which combines the quantitative and qualitative approaches). The sample consisted of (4) kindergarten supervisors. The study tools consisted of a questionnaire distributed to the teachers and principals of the study sample and an interview with kindergarten supervisors in the directorates of education in the Nablus governorate. Kindergarten teachers and principals were of a medium degree, and the study showed that there were no statistically significant differences between the averages of the responses of the study sample due to the variables (kindergarten type, job, years of experience, and educational qualification) for all fields of study, and the total score, and there were statistically significant differences between The average responses of kindergarten teachers and principals in the first field are attributed to the educational qualification variable in favor of postgraduate studies, and there were no statistically significant differences between the averages of the students. The answers of the study sample individuals are attributed to the variable of training courses in the field of teaching reading in the areas of difficulties related to the child, and difficulties related to the principal, while there are statistically significant differences between the average responses of the study sample due to the variable of training courses in the field of teaching reading in the field of difficulties related to the teacher, and the total score, in favor of "There are training courses in the field of teaching reading." The study recommended the need to conduct training courses for female teachers. In order to know how to deal with students who have difficulties in learning reading skills, and the need to employ specialized teachers in kindergartens in order to develop an appropriate treatment plan to treat weaknesses, and to rehabilitate schools with special tools and teaching aids to treat difficulties in reading skills
Keywords: Difficulties Learning; Reading Skills; Reading; Kindergarten Students